Formulation based on essential oils of three plant spies for the control of Tribolium castaneum in stored foodstuffs - Azeb Atmane Serine; Ben Amor Lina (جامعة الوادي university of eloued, 2025)
The primary objective of this work is to develop a natural formulation with insecticidal effectiveness against storage material pests, specifically targeting the flour beetle Tribolium castaneum. In this context, the toxicity of plant extracts from Neem (Azadirachta indica) seeds, Harmal (Peganum harmala) seeds, and Asafoetida (Ferula assa-foetida) gum was tested separately against adult flour beetles Tribolium castaneum at different increasing concentrations, and a mixture of these plant extracts was also evaluated. An essential oil formulation was applied using contact and fumigant methods at doses of (0.5 μl/ml, 1.5 μl/ml, 3 μl/ml, and 6 μl/ml). Mortality rates were observed in the first hour of treatment initiation and after 24 hours, with a 100% mortality rate recorded. Similarly, an alcoholic formulation of plant extracts from Neem(Azadirachta indica) seeds and Harmal( Peganum harmala) seeds was tested using contact and fumigant methods at doses of (0.5 μl/ml, 1 μl/ml, 2.5 μl/ml, and 5 μl/ml), and mortality rates were observed at 1 hour and 24 hours. A 100% mortality rate was recorded within the first 24 hours. According to our findings, the recorded mortality rate varied depending on the dose, exposure duration, and plant species. The efficacy of the formulation containing a mixture of Neem, Asafoetida, and Harmal plant extracts together was more potent and faster-acting compared to the toxicity of each extract individually.
Plant Production
Keywords: Natural formulation; Plant extracts; Alcoholic extract; Essential oils; Tribolium castaneum; Peganum harmala; Azadirachta indica; Ferula assa-foetida.